Gestión de la Propiedad, Planta y Equipo vinculada al Área de Producción de la Empresa Pellikari S.A. - García Miranda, Karolina de los Ángeles (2021)
The case study "Management of Property, Plant and Equipment linked to the Production Area of the Company Pellikari S.A." assesses the execution of control over these assets belonging to the company under study, where physical information is the main source for determining the problems that affect the company. These assets of the banana company, constitute the productive and commercial operation of the same, the most relevant results of our case analysis is aimed at identifying the lack of treatment and control in the management of Property, Plant and Equipment, as they are deficient existing procedures. For this, a methodology with an inductive approach was used through techniques such as observation, interview and survey directed to administrative personnel and operators that allowed to know the individual and general problem.